2015
DOI: 10.1186/s13256-015-0621-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic treatment of colorectal cancer in pregnancy: case report

Abstract: IntroductionColon cancer in pregnancy is uncommon. Only a small number of case reports have been published in the literature on the use of chemotherapeutic drugs during pregnancy. Reports of such cases assist clinicians in further investigating the use of chemotherapy in pregnancy.Case presentationFOLFOX-6 was administered to a pregnant, 33-year-old Saudi woman with metastatic colon cancer from 22 to 30 weeks of gestation. Her cancer was diagnosed during her pregnancy. She tolerated the chemotherapy well and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 32 publications
(47 reference statements)
2
32
0
2
Order By: Relevance
“…From an obstetrical point of view, both the timely and safe resolution of childbirth and fetal well-being must be ensured in the sense that neither the cancer nor its treatment seriously affects the condition of the fetus and the newborn. Obviously, is not wise to administrate chemotherapy during first trimester, but there are a lot of drugs that can be used after fetal development [10,11]. The most important complication could be a fetal growth restriction, but, while it would be only a restriction and not a lack of fetal growth and the Doppler evaluations reassured the fetal state, is possible to continue the pregnancy to the most advanced gestational age as possible, as we have done with this two cases of colon cancer and we have done with other cancers, specially breast cancer and pregnancy.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…From an obstetrical point of view, both the timely and safe resolution of childbirth and fetal well-being must be ensured in the sense that neither the cancer nor its treatment seriously affects the condition of the fetus and the newborn. Obviously, is not wise to administrate chemotherapy during first trimester, but there are a lot of drugs that can be used after fetal development [10,11]. The most important complication could be a fetal growth restriction, but, while it would be only a restriction and not a lack of fetal growth and the Doppler evaluations reassured the fetal state, is possible to continue the pregnancy to the most advanced gestational age as possible, as we have done with this two cases of colon cancer and we have done with other cancers, specially breast cancer and pregnancy.…”
Section: Commentsmentioning
confidence: 99%
“…There are few reports about these cases. Makoshi et al [2] reported a case treated with FOLFOX-6 to a pregnant woman between 22 and 30 gestational weeks. The patient tolerated well the treatment and was delivered of a term newborn without any harm.…”
Section: Introductionmentioning
confidence: 99%
“…Cetuximab, panitumumab, bevacizumab, ramucirumab, and ziv-aflibercept are IgG subclass monoclonal antibodies or fusion proteins and may follow this same fetal exposure pattern [7, 37, 49-51, 53, 54]. [20,21,47,48] 587-677.19 (SN-38 5 392) D Human data: 2 cases given 5-FU in 2nd and 3rd trimester report no congenital malformations Animal data: embryotoxic, teratogenic, decreased learning, and low birth weights Oxaliplatin [15][16][17][18][19]46] 397.3 D Human data: 5 cases given 5-FU in 2nd and 3rd trimester report limited congenital malformations (1 case of hypothyroidism) Animal data: embryo-fetal toxicity and teratogenic Bevacizumab [37,49] 149,000 C Human data: no i.v. administration data Animal data: teratogenic, fetal resorptions, reduced maternal and fetal weights Ziv-Aflibercept [50] 97,000 C Human data: none Animal data: embryo-fetal toxicity and teratogenic effects Cetuximab [37,53] 152,000 C Human data: none Animal data: embryolethal and abortifacient effects Panitumumab [37,54] 147,000 C…”
Section: Timing Of Drug Administrationmentioning
confidence: 99%
“…A concern with extrapolation from these cases is the route of administration; bolus dosing is used with FAC, whereas 5-FU in CRC is given as both a bolus and continuous infusion. No congenital abnormalities, except for hypothyroidism, were found in 8 pregnant women with CRC who received 5-FU alone or in combination (with oxaliplatin or irinotecan) after the first trimester (Table 3) [15][16][17][18][19][20][21][22]. Capecitabine was given in one case of CRC during pregnancy, along with oxaliplatin, in the first trimester [13, 23].…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation